2335. Acinetobacter baumannii Infection—Clinical Profile, Drug Resistance, and Presence of Virulence Factor AdeRS: Experience From a Pediatric Tertiary Care Centre in North India. (26th November 2018) - Khurana, Prerna; Saigal, Karnika; Ghosh, Arnab; Dhingra, Dhulika; Jajoo, Mamta; Mohta, Anup
Abstract: Background: Acinetobacter baumannii has emerged as an important opportunistic pathogen. Its ability to develop resistance to multiple antibiotics leaves few treatment options. AdeRS, a two-component regulatory system, which controls expression of the adeABC efflux pump is involved in multidrug resistance. There is lack of data regarding presence of virulence factors leading to antimicrobial resistance and their correlation with the outcome of the patients. The study was done to evaluate the prevalence of virulence factors AdeRS gene responsible for the accentuation of drug resistance, and correlation with the clinical outcome of the patient. Methods: Clinical details of 80 patients with labeled A. baumannii infection were collected and analyzed with the resistance patterns of the isolates and molecular detection of the AdeRS virulence gene. Results: 80 patients with labeled A. baumannii infection were included in the study. Most common presentation among patients with A. baumannii was pneumonia (46.25%) followed by sepsis. 63.75% of patients were admitted in the ICU. Neonates were mostly affected. Of the total 37 neonates with A. baumannii infections, 26 were hospital acquired. Mean weight of neonates with infection was 2.1 kg. 45.9% neonates with A. baumannii infections had undergone surgery for congenital anomalies. Sepsis was the most common presentation among neonates. Overall, mortality was 41.25%. The maximum mortality was among neonates (57.6%). Children presenting with sepsis had a higher mortality. Mortality in ICU patients was 78.8% compared with 21% in the wards. Average length of stay in the hospital after acquisition of A. baumannii infection was 20.2 days. Of the total 80 isolates, 2.5% were MDR and 86.25% were XDR strains. AdeRS was present in 90% of the isolates. All the isolates with XDR pattern of drug resistance had AdeRS gene. 27.5% of the isolates were tigecycline resistant and AdeRS gene was present in all them. Thirty-three patients who died all possessed AdesRS gene and were XDR strains. Conclusion: A. baumannii is responsible for a substantial percentage of nosocomial infections. Presence of AdeRS gene reduces the susceptibility to large number of drugs and thus selects out XDR A. baumannii with high mortality rates in the hospital settings, leaving efflux pump inhibitors as the therapy of choice. Disclosures: All authors: No reported disclosures.